LGBTQ cultures : what health care professionals need to know about sexual and gender diversity - Eliason, Michele J.; Chinn, Peggy L. (Wolters Kluwer, 2018)
Drawn from real-world experience and current research, the fully updated LGBTQ Cultures, 3rd Edition paves the way for healthcare professionals to provide well-informed, culturally sensitive healthcare to lesbian, gay, bisexual, transgender, and queer (LGBTQ) patients. vital guide fills the LGBTQ awareness gaps, including replacing myths and stereotypes with facts, and measuring the effects of social stigma on health. Vital for all nursing specialties, this is the seminal guide to actively providing appropriate, culturally sensitive care to persons of all sexual orientations and gender identities. -- Provided by publisher.